Consumers' Perceptions and Preferences toward Florida Orange Juice: FE1110, 12/2021 - Heng, Yan; House, Lisa; Yoon, Sungeun (EDIS, 2021)
Faced with reduced domestic supply, competition from imports, and high production costs, the Florida citrus industry and Florida growers need to understand how consumers perceive Florida-produced orange juice and whether they value it more than OJ produced elsewhere. We conducted a national survey to understand consumers' perceptions and confirmed that consumers have a superior perception of Florida OJ, which could lead to higher rates of willingness-to-buy and willingness-to-pay.